Antimicrobial abietane-type diterpenoids from Torreya grandis. (September 2022) - Cui, Jiao-Jiao; Li, Wei-Jia; Wang, Cheng-Lei; Huang, Yi-Qi; Lin, Wei; Zhou, Bin; Yue, Jian-Min
Abstract: Twelve undescribed abietane-type diterpenoids, along with ten known analogues were isolated from the twigs and leaves of Torreya grandis var. merrillii Hu. Their structures were characterized by spectroscopic data analyses, single-crystal X-ray diffraction, and ECD spectra. Torgranols A–C possess three different architectures shaped via a common 6, 7- seco -procedure and subsequent ring formations. In particular, torgranol A represents the first example of a 6, 7- seco -abietane diterpenoid featuring a unique oxygen bridge between C-3 and C-6. The biosynthetic pathways for torgranols A–C were proposed. Some compounds displayed antimicrobial activities against Mycobacterium tuberculosis and/or Staphylococcus aureus . Graphical abstract: Twelve undescribed abietane-type diterpenoids, along with ten known analogues were isolated from Torreya grandis var. merrillii Hu, and some of them showed antimicrobial activities. Image 1 Highlights: Twelve undescribed abietane diterpenoids were isolated from Torreya grandis. Torgranol A is a 6, 7- seco -abietane diterpenoid with a unique tetrahydrofuran ring. The biosynthesis of torgranols A–C was proposed with two common precursors. Some compounds showed antimicrobial activities.